A differentiated approach to the management of patients with hyperplastic diseases of the uterus complicated by abnormal uterine bleeding - I. Lomakina; N. Rozhkovska; V. Sytnikova; S. Syviy (Kazimierz Wielki University, 2023)
The purpose: to justify a differentiated approach to the management of patients with hyperplastic uterine diseases complicated by abnormal uterine bleeding (AUB) based on the study of the morpho-functional features of the endo- and myometrium. It has been shown that PgR expression is low in patients with combined lesions of the endometrium and myometrium complicated by AMC. The degree of PgR expression has a strong negative correlation with pathological changes of the endometrial-myometrial junction (r=-0.71), which made it possible to consider these criteria in the creation of a differentiated algorithm for the management of patients taking into account clinical and morphological pathogenetic variants of the disease. The use of differentiated approaches to the treatment of patients with combined hyperplastic processes of the uterus, taking into account the clinical and morphological features of the disease, made it possible to reduce the number of recurrences of AMC and achieve a long-term clinical effect in comparison with traditional treatment.